REVITALIZING THE ROLE OF TEACHERS IN ENHANCING THE EFFECTIVENESS OF ISLAMIC RELIGIOUS EDUCATION IN THE DIGITAL ERA - Wardana, Tirta Rega; Arifin, Zainal; Roisyah, Hannina (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study investigates the transformation of Islamic Religious Education (PAI) teachers' roles in the digital era, focusing on how they integrate technological advancements while maintaining the core values of Islamic education. Conducted as a qualitative case study at Pondok Pesantren Nurul Chotib Al-Qodiri 4, the research involved interviews, observations, and documentation analysis with asatid (teachers) and santri (students). The findings reveal that PAI teachers are evolving from traditional knowledge transmitters into multidimensional educators who also serve as moral exemplars and digital facilitators. Teachers are required to enhance their digital literacy, utilizing tools such as educational videos, digital Qur'an applications, and online platforms to deliver more relevant and engaging religious instruction. However, the study highlights that technological integration must be balanced with emotional engagement to preserve meaningful teacher-student relationships. The research offers a novel analytical framework linking spiritual values, teacher roles, and digital strategies, emphasizing the importance of continuous professional development. Despite its contributions, the study is limited by its narrow institutional focus and participant demographics. Future research should expand to various educational settings and adopt broader methodologies to generalize findings. Overall, the integration of technology into Islamic education is shown to be both an opportunity and a challenge, requiring a holistic approach that harmonizes tradition with innovation. Penelitian ini mengkaji transformasi peran guru Pendidikan Agama Islam (PAI) di era digital, dengan fokus pada bagaimana mereka mengintegrasikan kemajuan teknologi sambil mempertahankan nilai-nilai inti pendidikan Islam. Penelitian ini dilakukan dengan pendekatan studi kasus kualitatif di Pondok Pesantren Nurul Chotib Al-Qodiri 4, yang melibatkan wawancara, observasi, dan analisis dokumentasi dengan asatid (guru) dan santri (siswa). Temuan penelitian menunjukkan bahwa peran guru PAI berkembang dari sekadar penyampai pengetahuan menjadi pendidik multidimensi yang juga berfungsi sebagai teladan moral dan fasilitator digital. Guru dituntut untuk meningkatkan literasi digital mereka, dengan memanfaatkan alat seperti video pembelajaran, aplikasi Al-Qur'an digital, dan platform daring untuk menyampaikan materi agama yang lebih relevan dan menarik. Namun, penelitian ini juga menyoroti bahwa integrasi teknologi harus diimbangi dengan keterlibatan emosional untuk mempertahankan hubungan guru-siswa yang bermakna. Penelitian ini menawarkan kerangka analisis baru yang mengaitkan nilai-nilai spiritual, peran guru, dan strategi digital, dengan menekankan pentingnya pengembangan profesional berkelanjutan. Meskipun demikian, penelitian ini memiliki keterbatasan dalam lingkup institusi dan demografi peserta, sehingga disarankan penelitian lanjutan dengan metodologi yang lebih luas dan melibatkan berbagai latar belakang institusi serta jenjang pendidikan. Secara keseluruhan, integrasi teknologi dalam pendidikan agama Islam terbukti menjadi peluang dan tantangan, yang memerlukan pendekatan holistik yang mengharmoniskan tradisi dengan inovasi.